2004
DOI: 10.1152/ajpcell.00389.2003
|View full text |Cite
|
Sign up to set email alerts
|

Na+ pump α2-isoform specifically couples to contractility in vascular smooth muscle: evidence from gene-targeted neonatal mice

Abstract: The relative expression of alpha(1)- and alpha(2)-Na(+)/K(+)-ATPase isoforms found in vascular smooth muscle is developmentally regulated and under hormonal and neurogenic control. The physiological roles of these isoforms in vascular function are not known. It has been postulated that the alpha(1)-isoform serves a "housekeeping" role, whereas the alpha(2)-isoform localizes to a subsarcolemmal compartment and modulates contractility. To test this hypothesis, isoform-specific gene-targeted mice in which the mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
94
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 53 publications
10
94
1
Order By: Relevance
“…The Paul laboratory, which previously reported that the ␣ 2 Na ϩ pump couples to contractility in the aorta (106), also reported that reduced ␣ 2 expression (␣ 2 ϩ/Ϫ ) accelerated the induction of DOCA-salt hypertension (107).…”
Section: How Does Low-dose Ouabain Augment Contractility?mentioning
confidence: 99%
See 3 more Smart Citations
“…The Paul laboratory, which previously reported that the ␣ 2 Na ϩ pump couples to contractility in the aorta (106), also reported that reduced ␣ 2 expression (␣ 2 ϩ/Ϫ ) accelerated the induction of DOCA-salt hypertension (107).…”
Section: How Does Low-dose Ouabain Augment Contractility?mentioning
confidence: 99%
“…In striking contrast, at least in some cells types, including vascular smooth muscle myocytes, neurons, and glia, ␣ 2 and ␣ 3 are confined to PM microdomains closely juxtaposed to the underlying sarco(endo)plasmic reticulum (SER) (56,57,106). Indeed, preliminary results suggest that ␣ 1 may be excluded from these junctional microdomains (65).…”
Section: How Does Low-dose Ouabain Augment Contractility?mentioning
confidence: 99%
See 2 more Smart Citations
“…There are four ␣-subunit isoforms (18). Na ϩ pumps with an ␣1 and those with an ␣2 are both expressed in astrocytes and in arterial myocytes (19)(20)(21). In both cell types, ␣2 Na ϩ pumps are confined to PM microdomains that overlie the jS͞ER, whereas ␣1 Na ϩ pumps are more uniformly distributed in the PM (22)(23)(24).…”
mentioning
confidence: 99%